Risk of Depression and Anxiety in Those Who Gave Birth to Children Who Developed Invasive Group B Streptococcal Disease: A Population-Based Cohort Study - Horváth-Puhó E; Chandna J; Paul P; Wilson CA; Sørensen HT; Lawn JE (Clinical Epidemiology)
Erzsébet Horváth-Puhó,1,* Jaya Chandna,2,3,* Proma Paul,2,3 Claire A Wilson,4,5 Henrik T Sørensen,1,* Joy E Lawn2,3,* 1Department of Clinical Epidemiology and Center for Population Medicine, Aarhus University and Aarhus University Hospital, Aarhus, Denmark; 2Maternal, Adolescent, Reproductive & Child Health (MARCH) Centre, London School of Hygiene & Tropical Medicine, London, UK; 3Department Infectious Disease Epidemiology and International Health, London School of Hygiene & Tropical Medicine, London, UK; 4Institute of Psychiatry, Psychology and Neuroscience, King’s College London, London, UK; 5South London and Maudsley NHS Foundation Trust, London, UK*These authors contributed equally to this workCorrespondence: Erzsébet Horváth-Puhó, Department of Clinical Epidemiology and Center for Population Medicine, Aarhus University and Aarhus University Hospital, Olof Palmes Allé 43-45, Aarhus, Aarhus N 8200, Denmark, Tel +45 87 16 72 12, Email ep@clin.au.dkBackground: Mental disorders such as depression and anxiety are common for women of reproductive age and impact pregnancy and parenting. Invasive Group B Streptococcus disease (iGBS) is a leading cause of neonatal morbidity and mortality worldwide. Little is known about the short and long-term risk of common mental disorders in birthing parents whose infants had iGBS in the first 89 days after birth. We aimed to examine the risk of depression and anxiety in birthing parents with iGBS-affected infants in a cohort study with prospectively collected data from Danish registries.Materials and Methods: Using Danish healthcare registries from 1997 to 2018, we obtained data on iGBS-affected children and their birthing parents. A comparison cohort was randomly sampled (1:50) through risk-set sampling, and matched on persons’ age, year of child´s birth, and parity. The risk of using antidepressant medicines and depression or anxiety diagnosis was analyzed with cumulative incidence function and in Cox proportional hazards regression models.Results: During the study period, we identified 1,552 women with iGBS-affected child and 76,879 matched comparators. During a median follow-up of 9∙9 years, the cumulative incidence of antidepressants use among birthing parents with iGBS-affected children was 31% (95% confidence interval, CI: 28– 34%), as compared with 29% (95% CI: 28– 30%) among members of the comparison cohort (hazard ratio 1∙12 [95% CI: 1∙01– 1∙25]). A 16% increase in the rate of diagnosed depression or anxiety was observed in the overall follow-up period.Conclusion: Our findings provide evidence of a slightly increased risk of antidepressant use and diagnosed depression or anxiety in parents who gave birth to children with a history of iGBS compared to a matched cohort of birthing parents whose infants did not develop iGBS. Our findings highlight the importance of addressing the mental health needs of birthing parents affected by their children’ iGBS.Keywords: Streptococcus agalactiae, group B Streptococcus, antidepressant, depression, anxiety, cohort study